OP28 THE ROLE OF GENDER IN CNS TUMOUR INCIDENCE AND SURVIVAL - Mathew, R.K. (Oxford University Press, 2014)
INTRODUCTION: Evidence exists, in germ cell tumours (GCT) and medulloblastoma subcategories, that gender significantly influences incidence and outcome - perhaps through susceptibility to tumour genesis, and sensitivity to treatment. The role of gender in other CNS tumours is unclear. METHOD: Age-adjusted incidence (2000-2007) and overall survival (OS, 1998-2007) rates were collected from the Surveillance Epidemiology and End Result (SEER) registry (covering 28% of US patients) for common CNS tumours in age epochs ranging 0-80 years. Patients with histologically confirmed, ICD-03 coded, first tumours, were included. Mortality was defined as any cause of death within 1- or 5-years of diagnosis. Results were statistically analysed by Incidence Rate Ratio (IRR), Kaplan-Meier and Log Rank (Cox Proportional Regression Hazard) Testing (p < 0.05). RESULTS: Significantly higher incidence was observed in males with grade II astrocytomas (IRR 1.19), high grade gliomas (IRR 1.18-1.26), oligodendrogliomas (IRR 1.12), lymphoma (IRR 1.18), embryonal (IRR 1.17-1.21), and GCTs (IRR 1.51) (all p < 0.05). No significant difference in incidence was seen between gender in pilocytics, ependymomas and meningiomas. 1- and 5-year OS was better in; older females with meningiomas, oligodendrogliomas and ependymomas; younger males with anaplastic astrocytomas. 5-year OS was better in; females aged <5 years with ependymomas, females aged 10-24 years with medulloblastomas; females aged 20-39 with grade II astrocytomas. CONCLUSION: Gender is a significant factor in predisposing to certain CNS tumours and treatment response - possibly through epigenetic and hormonal differences. Further investigation is needed.